Looking for Ocular Tuberculosis: Prevalence and Clinical Manifestations of Patients with Uveitis and Positive QuantiFERON®-TB Gold Test. (18th August 2018) - Pathanapitoon, Kessara; Kunavisarut, Paradee; Sirirungsi, Wasna; Rothova, Aniki
ABSTRACT: Purpose : To report on the prevalence of ocular TB and positive QuantiFERON ® -TB Gold (QFT-G) test in uveitis patients and describe their clinical manifestations. Methods : We performed a prospective study of 108 new human immunodeficiency virus-negative uveitis patients. All patients underwent a tailored screening protocol for uveitis and received QFT-G test and tuberculin skin tests (TST). Results : QFT-G test was positive in 39/108 (36%) of patients, while TST ≥15 mm was positive in 16/108 (15%) patients. None of the patients were identified with active systemic TB. Out of 39 QFT-G-positive patients, 25 (64%) were of unknown cause, which represents a higher proportion than encountered in QFT-G-negative cases (29/69; 42%; p <0.03). Retinal occlusive vasculitis was frequently observed in patients with positive QFT-G outcomes (10/39 vs 3/69; p = 0.001) and was commonly associated with high QFT-G levels, young age, and male gender. Conclusions : Out of all patients with uveitis, none had active systemic TB but 36% were positive for QFT-G test. QFT-G-positive patients frequently had uveitis of unknown cause and exhibited clinical features of occlusive retinal vasculitis.